2011
DOI: 10.1097/md.0b013e3182259d38
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fluconazole in the Treatment of Candida Endocarditis

Abstract: The treatment of Candida infective endocarditis generally involves infected valve removal accompanied by antifungal therapy with amphotericin B or a lipid-based derivative, with or without flucytosine. While often used as chronic suppressive therapy in these patients, the precise role for fluconazole has not been established. We conducted a meta-analysis of 64 literature cases of Candida endocarditis whose management did not include valve replacement but who received fluconazole, alone or concurrently or in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 74 publications
2
32
0
6
Order By: Relevance
“…240,241 The well-recognized risk factors associated with fungal IE (eg, IDU and immunocompromised state) have become less prevalent compared with the presence of a cardiovascular device, including central venous catheters, permanent pacemakers and defibrillators, and prosthetic valves. [240][241][242][243][244][245][246] Fungal IE has been recognized as a cause of early PVE, but a case series from a single medical center demonstrated that 43% of these cases had symptom onset >1 years after prosthetic valve placement. 242 In contrast to the expected older age predilection for the development of IE, patients with fungal IE have been younger, which was somewhat unanticipated, considering the low prevalence of IDU among the cohort.…”
Section: Fungimentioning
confidence: 99%
See 1 more Smart Citation
“…240,241 The well-recognized risk factors associated with fungal IE (eg, IDU and immunocompromised state) have become less prevalent compared with the presence of a cardiovascular device, including central venous catheters, permanent pacemakers and defibrillators, and prosthetic valves. [240][241][242][243][244][245][246] Fungal IE has been recognized as a cause of early PVE, but a case series from a single medical center demonstrated that 43% of these cases had symptom onset >1 years after prosthetic valve placement. 242 In contrast to the expected older age predilection for the development of IE, patients with fungal IE have been younger, which was somewhat unanticipated, considering the low prevalence of IDU among the cohort.…”
Section: Fungimentioning
confidence: 99%
“…After completion of this initial therapy, long-term (lifelong) suppressive therapy with an oral azole is reasonable. 243,244,246 Suppressive therapy has been used in 2 populations. First, because of the high relapse rate of fungal IE and the prolonged delay (years in some cases) in relapse, oral azoles have been administered after combined medical and surgical induction therapy.…”
Section: Fungimentioning
confidence: 99%
“…Dominują zakażenia Candida i Aspergillus spp. Te ostatnie objawiające się jako IZW z ujemnymi posiewami krwi [199,200]. Śmiertelność jest bardzo wysoka (> 50%), a leczenie wymaga skojarzonej terapii przeciwgrzybicznej i chirurgicznej wymiany zastawki Opcjonalnie można dołączyć streptomycynę (15 mg/kg/24 h w 2 dawkach) przez pierwsze kilka tygodni; c Doksycyklina w skojarzeniu z hydroksychlorochiną (z monitorowaniem stężenia hydroksychlorochiny w osoczu) jest istotnie skuteczniejsza niż doksycyklina w monoterapii [194];…”
Section: Grzybyunclassified
“…Dawki podawanych leków są takie same jak w przypadku IZW spowodowanego gronkowcami lub eneterokokami (tab. 16 i 18) [196,197] [135,[198][199][200]. Leczenie przeciwgrzybicze w przypadku IZW spowodowanego przez Candida obejmuje liposomalną amfoterycynę B (lub inne preparaty lipidowe) łącznie z (lub bez) flucytozyną lub echinokandyną w dużych dawkach.…”
Section: Grzybyunclassified
See 1 more Smart Citation